Trace Metals in the Environment New Approaches and Recent Advances - Alfonso Murillo-Tovar, Mario; Saldarriaga-Noreña, Hugo; Saeid, Agnieszka (IntechOpen, 2021)
The occurrence of heavy metals in the environment, even in traces, represents a severe risk for the ecosystems and can be dangerous to human health. However, a better understanding of the main aspects involved is still needed to reduce its negative impact on the environment and health. This book covers the recent methods used for the evaluation of heavy metal pollution and the identification of its sources, descriptions of some of the processes involved in its mobility and transport, attempts to address health and environmental effects of heavy metals pollution, and presents alternative technologies for its removal and remediation from environmental samples. Therefore, this book is recommended for experts in the comprehensive management of metal contamination in different environmental compartments.